Solvent - Free Synthesis of Substituted Dicarboxylic Acids from Stobbe Condensation: A Novel Approach - Banerjee, Shubhra; Chari, Bhagyashree; Tayde, Ravibabu (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
During the last few years, solvent-free reactions for different organic syntheses have been a field of increasing interest in synthetic organic chemistry because of their ease of occurrence. The present work depicts a unique one-pot synthesis method in which solvent-free conditions allow for improving the yield and expediting the reaction. Solvent-free Stobbe condensation of furfural with dimethyl succinate under anhydrous conditions at room temperature using dry-solid potassium tertiary butoxide gave 3-carbomethoxy, 4-furyl-3-butenoic acid, which upon methylation followed by Stobbe condensation reaction with different aldehydes and/or ketones under anhydrous conditions at room temperature afforded substituted carbomethoxy acids 5a–f. These acid ester products were saponified to the corresponding dicarboxylic acids 6a–f which are useful in the synthesis of photochromic fulgides. It was concluded that the solvent-free condensations of substituted ketones and/or aldehyde with dimethyl succinate at room temperature occurred smoothly to give substituted acid esters. Compared to the classical condensation method, which required a lot of solvents and chemicals, the green method used much fewer dry solid reagents, making it more economical.